Development system for FPGA-based digital circuits - Sklyarov, Valery (1999)
The paper discusses some new hardware and software tools that can be used for the design of virtual circuits based on dynamically reconfigurable FPGAs. With the aid of these tools we can implement a system that requires some hardware resources Rc, on available hardware that has resources Rh, where Rc>Rh. The main idea of the approach supported by these tools is the rational combination of FPGA capabilities with some proposed methods for producing a modifiable specification, together with a novel technique for architectural and logic synthesis, which has been incorporated into the new design environment.